Impact of stress on health cognitions and behaviours - Madihah Mohamad Shukri (United Kingdom : The University of Leeds, 2012)
The present thesis attempts to extend the knowledge of stress- health behaviours relationships by integrating social cognitive variables (i.e. from the TPB model) into the study of stress. This thesis also aims to elucidate how nationality and gender shape cognition, intention and health behaviour by utilizing samples representing both individualistic and collectivistic cultures (i.e. UK and Malaysia) and both genders.